REFLECTIONS ON AN AMERICAN’S JOURNEY TO ISLAM: A SOCIO-CULTURAL ANALYSIS OF DA’WAH METHODOLOGY - Sawyer M. French (Jurnal MD, 2017)
Da’wah among non-Muslims as a practice necessitates the development of cross-cultural understanding. Attempts to draw non-Muslims towards Islam will be largely fruitless without taking into account strategic concerns regarding the dominant rhetorical and interpersonal traits of the unique cultures in which they live. In this paper, I present a narrative on my personal journey to Islam and discuss the implications it holds for da’wah strategies among non-Muslims in an American context, while acknowledging the vast diversity within this sphere. I make an analytical distinction between values particular to Islam, like the ṣhalāt prayers and the ḥajj pilgrimage, and universal values, like kindness and social justice. Based on my experience, I argue that an emphasis on Islam’s universal values will create far more appeal among non-Muslims, as their existing value systems place no importance on rituals such as ṣhalāt. In the American cultural and political context, I insist that overt da’wah will be counter-productive and drive non-Muslims away, whereas da’wah given by good example will - although less effective in the short term - be more fruitful overall. The best da‘is are those who live out and pursue the social ideals of Islam, regardless of whether or not they even intend to conduct da’wah. While the specific conclusions which provided in this paper in an American context, I argue that da’wah in any unique cultural context requires socio cultural analysis in order to maximize da’wah efficiency.